Spatial analysis of cases of Tuberculosis with Mental Disorders in São Paulo - Luiz Arroyo Henrique Arroyo; Marcos Augusto Moraes Arcoverde; Josilene Dália Alves; Miguel Fuentealba-Torres; Denisse Cartagena-Ramos; Alessandro Rolim Scholze; Antônio Carlos Vieira Ramos; Ricardo Alexandre Arcêncio
ABSTRACT Objective: To analyze the spatial distribution of Tuberculosis cases with Mental Disorders, identifying factors that determine its occurrence. Method: Ecological study, conducted in the municipalities of São Paulo State. Secondary data were used, with the incidence of Tuberculosis and Mental Disorders as dependent variables in the years 2012 to 2015 and independent variables, socioeconomic, health and income transfer data. The Geographically Weighted Regression was applied in this study. Results: It was observed a distinct distribution between cases of Tuberculosis and Mental Disorders in the municipalities of São Paulo State. Among the explanatory factors, the Primary Care Coverage, population of freedom and income inequality were spatially associated with Mental Illness (R2= 0.12); Alcoholism (R2= 0.12) Illicit Drugs (R2= 0.50) and Smoking (R2= 0.50). Conclusion / Final considerations: The study advances in knowledge by evidencing the spatial distribution of cases of Tuberculosis and Mental Disorders, evidencing the determining factors for its occurrence in São Paulo State.